Analisis Realisme Magis dalam Novel Srimenanti Karya Joko Pinurbo - Liani, Dwi Retno; Sutejo, Sutejo; Novitasari, Lusy (STKIP PGRI Ponorogo Press, 2024)
Magical realism is a fusion of elements of realism with fantasy or imagination beyond reason, which often occurs in society due to the influence of culture and belief. Among the literary works that have these elements, one of them is the novel Srimenanti by Joko Pinurbo. The research was conducted using qualitative descriptive methods. The theory used in analyzing this novel is Wendy B. Fariz’s theory. The research results show that there are five characteristics of magical realism. These five characteristics include: irreducible elements in the form of belief in myths and supernatural figures (eltece); (2) the phenomenal world in the form of belief in the tradition of the spirit month and the existence of God (religion); (3) doubts caused by figures supernatural (eltece) and magical objects in the form of painting equipment; (4) Merger of Territories in the form of a magical figure (elence) acting like a human; (5) Cracks in Time, Space, and Identity in the form of cracks in space, namely, guard posts, and identity cracks, happen to the character Srimenanti, who has an identity as a painter and a holy person, and the character Uncle Yusi as a teacher and spiritual advisor.